The double-edged sword of legitimacy in base-of-the-pyramid markets - Kistruck, Geoffrey M.; Webb, Justin W.; Sutter, Christopher J.; Bailey, Anastasia V.G. (Journal of Business Venturing, 2015)
As compared to developed countries, a much higher proportion of entrepreneurs within base-of-the-pyramid (BOP) markets operate unregistered businesses. Prior research has suggested that the primary cause of such informal activity in these settings is the general failure of ‘weak’ institutions to provide sufficient resources to warrant formalization. We attempt to extend such thinking by deconstructing the discrete and inter-related effects of formal business registration on the level of resources obtained by entrepreneurs from financial, labor, and legal institutions within BOP markets. Using a multi-method approach involving 299 entrepreneurs within Guatemala City, our results suggest that being seen as a ‘legitimate’, registered business can actually lead to both increased resource provision and resource appropriation. More specifically, adhering to the norms and rules prescribed by regulatory institutions within weak legal environments can convey positive signals of stability and profitability that both attract the desired attention from formal institutional actors, as well as unwanted attention from criminals.